Dermatoses among athletes - Jakubczak, Zofia; Zimniak, Maria; Miłkowski, Paweł; Głąbień, Marta; Kusiak, Karolina; Aleksandrowicz, Daria; Kuśnierz, Anna; Wieczorek, Olga; Kondratowicz, Aneta; Śliwiak, Patryk (Quality in Sport, 2024)
Introduction: Dermatoses are a common problem among athletes due to exposure to various chemical substances, close skin contact with other individuals and higher risk of abrasions and skin trauma. Dermatoses affecting athletes may be divided to inflammatory, infectious and mechanical dermatoses. Due to various presentations, athletes should not neglect any lesions on their skin and should seek medical help. Physicians must remember about thorough examination including skin, to check if athletes can exercise and participate in sport events. Purpose of work: The aim of this article is to emphasize the association between dermatoses and sport activities, including the necessity of their proper diagnosis and treatment. Materials and methods: Articles in Pubmed database were researched using following keywords: dermatoses among athletes, sport dermatoses, infections among athletes, exercise-induced anaphylaxis. Conclusions: Skin diseases may affect athletes’ performance and require them to cease professional training and close contact with other athletes. Physicians must remember the necessity of an accurate diagnosis and prompt initiation of the treatment to avoid delay in practice, team training and competitions.